Photoelectric properties of modified C₆₀ films. Maxwell-Vagner type polarization between near-electrode and bulk layers - Koval'chuk, A.V.; Shevchuk, A.F.; Naiko, D.A.; Koval'chuk, T.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Within the frequency interval of 10⁻¹ to 10⁶ Hz investigated were the frequency dependences of the capacitance C and resistance R for modified С60 films in darkness and on exposure to the focused white light. A clamping ITO electrode with an intermediate layer of isotropic liquid (glycerin or distilled water) was taken instead of the traditionally used deposited top metal electrode. Found are the conditions when C and R changes are caused by near-electrode (f < 10³ Hz) and bulk (f > 10⁴ Hz) processes. It was shown that the sharp reduction of C and R with growing the frequency corresponds to the transition from one condition to the other, and such process can be described with account of the “classical” Maxwell-Wagner mechanism of interlayer polarization. The relaxation time of such process was found to be equal approximately 10 ns. This time was shown to depend on the manufacturing technology of С₆₀ films. Having analyzed the obtained frequency dependences of C and R, an equivalent circuit of the sample was suggested. We estimated the thicknesses of the liquid layer (≈ 30 µm) and near-electrode layer of С₆₀ films (tens of nanometers). Comparing the frequency dependences of C and R on exposure to light of the bottom and top electrodes, it was assumed that the С₆₀ films under laser UV-irradiation is non-uniform in thickness.